Knowledge sharing with a new dimension - Setiarso, Bambang (2006)
The purpose of this an article is to gain a better understanding of how some factors are critical for the successful application of knowledge sharing.Knowledge Sharing with a new dimension covers a wide range of functionalities and support different sets of activities. Therefore, to achieve knowledge sharing, this work limits the field of investigation to that Knowledge Sharing models, devoted to the formalization and sharing of best practices and experiences within the organization.Usability issues should be considered during the model of knowledge sharing in order to build systems which people with limited technological skills and readily use, we discuss two key forms of knowledge sharing usability, interface usability and the human-computer- interaction has helped model knowledge sharing principles to improve interface usability.We cover the following phases with a new dimension: (1).The dimension shift is quite obvious with respect to knowledge sharing from an organizational perspective, (see Model I);(2).The communicative dimension of knowledge sharing is also increasingly relevant as a means of organizing learning processes as collaborative, cooperative, exchange knowledge processes, (see Model III).(3). Knowledge sharing in the communicative dimension which at least with respect to the topic, self-organizing paradigm will have major consequences for librarians work and the structure and information transfer institutions, see Model IV and V).The outcome of this empirical research provides indications KS on a new dimension for the effective development and management of KS through key success factor such as dependent on both internal and external KS and interaction.